Functional siloxanes with photo-activated, simultaneous chain extension and crosslinking for lithography-based 3D printing. (12th September 2018) - Sirrine, Justin M.; Meenakshisundaram, Viswanath; Moon, Nicholas G.; Scott, Philip J.; Mondschein, Ryan J.; Weiseman, Tobin F.; Williams, Christopher B.; Long, Timothy E.
Abstract: A novel, poly(dimethyl siloxane)-based photopolymer that exhibits simultaneous linear chain extension and crosslinking was suitable for vat photopolymerization additive manufacturing. Photopolymer compositions consisted of dithiol and diacrylate functional poly(dimethyl siloxane) oligomers, where simultaneous thiol-ene coupling and free radical polymerization provided for linear chain extension and crosslinking, respectively. Compositions possessed low viscosity before printing and the modulus and tensile strain at break of a photocured, higher molecular weight precursor after printing. Photorheology and soxhlet extraction demonstrated highly efficient photocuring, revealing a calculated molecular weight between crosslinks of 12, 600 g/mol and gel fractions in excess of 90% while employing significantly lower molecular weight precursors (i.e. < 5300 g/mol). These photocured objects demonstrated a 2× increase in tensile strain at break as compared to a photocured 5300 g/mol PDMS diacrylamide alone. These results are broadly applicable to the advanced manufacturing of objects requiring high elongation at break. Graphical abstract: Highlights: Low viscosity photopolymer demonstrated properties of higher molecular weight precursors after photocuring. Thiol-ene coupling and acrylamide homopolymerization enabled simultaneous linear molecular weight growth and crosslinking. Vat photopolymerization additive manufacturing (3DP) enabled 3D fabrication. Photocured films demonstrat increase in molecular weight between crosslinks and tensile strain at break vs. control. Photocured, chain-extended oligomers maintained gel fractions in excess of 90%.